A revised cranial description of Massospondylus carinatus Owen (Dinosauria: Sauropodomorpha) based on computed tomographic scans and a review of cranial characters for basal Sauropodomorpha - Kimberley E.J. Chapelle; Jonah N. Choiniere (PeerJ, 2018)
Massospondylus carinatus is a basal sauropodomorph dinosaur from the early Jurassic Elliot Formation of South Africa. It is one of the best-represented fossil dinosaur taxa, known from hundreds of specimens including at least 13 complete or nearly complete skulls. Surprisingly, the internal cranial anatomy of M. carinatus has never been described using computed tomography (CT) methods. Using CT scans and 3D digital representations, we digitally reconstruct the bones of the facial skeleton, braincase, and palate of a complete, undistorted cranium of M. carinatus (BP/1/5241). We describe the anatomical features of the cranial bones, and compare them to other closely related sauropodomorph taxa such as Plateosaurus erlenbergiensis, Lufengosaurus huenei, Sarahsaurus aurifontanalis and Efraasia minor. We identify a suite of character states of the skull and braincase for M. carinatus that sets it apart from other taxa, but these remain tentative due to the lack of comparative sauropodomorph braincase descriptions in the literature. Furthermore, we hypothesize 27 new cranial characters useful for determining relationships in non-sauropodan Sauropodomorpha, delete five pre-existing characters and revise the scores of several existing cranial characters to make more explicit homology statements. All the characters that we hypothesized or revised are illustrated. Using parsimony as an optimality criterion, we then test the relationships of M. carinatus (using BP/1/5241 as a specimen-level exemplar) in our revised phylogenetic data matrix.